The Influence of Academic Discourses on Medical Students' Identification With the Discipline of Family Medicine. (May 2015) - Rodríguez, Charo; López-Roig, Sofía; Pawlikowska, Teresa; Schweyer, François-Xavier; Bélanger, Emmanuelle; Pastor-Mira, Maria Angeles; Hugé, Sandrine; Spencer, Sarah; Lévasseur, Gwenola; Whitehead, Ian; Tellier, Pierre-Paul
<x xml:space="preserve">Abstract</x> Purpose To understand the influence of academic discourses about family medicine on medical students' professional identity construction during undergraduate training. Method The authors used a multiple case study research design involving international medical schools, one each from Canada, France, Spain, and the United Kingdom (UK). The authors completed the fieldwork between 2007 and 2009 by conducting 18 focus groups (with 132 students) and 67 semistructured interviews with educators and by gathering pertinent institutional documents. They carried out discursive thematic analyses of the verbatim transcripts and then performed within- and cross-case analyses. Results The most striking finding was the diverging responses between those at the UK school and those at the other schools. In the UK case, family medicine was recognized as a prestigious academic discipline; students and faculty praised the knowledge and skills of family physicians, and students more often indicated their intent to pursue family medicine. In the other cases, family medicine was not well regarded by students or faculty. This was expressed overtly or through a paradoxical academic discourse that stressed the importance of family medicine to the health care system while decrying its lack of innovative technology and the large workload-to-income ratio. Students at these schools were less likely to consider family medicine. Conclusions These results stress the influence of academic discourses on medical students' ability to identify with the practice of family medicine. Educators must consider processes of professional identity formation during undergraduate medical training as they develop and reform medical education.